Numerical results of Crank-Nicolson scheme on unsteady nano fluid under the effect of Prandtl, Mixed Convection, and Magnetohydrodynamics - Mohammad Ghani; Yolanda Norasia; Indira Anggriani; Mohamad Tafrikan; Zulaikha Zulaikha ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2022)
In this paper, we are interested in the numerical results on the temperature and velocity profiles over a sphere of unsteady nano fluid by dealing with the effect of Prandtl, mixed convection, and magnetohydrodynamics. We first employ the boundary layer theory to establish the continuity, momentum, and energy equations. We further solve those differential equations numerically by using the finite difference scheme of Crank-Nicolson and Thomas algorithm for the iteration technique. The temperature and velocity profiles are established graphically for the variations of Prandtl, mixed convection, and magnetohydrodynamics. The velocity profile decreases when the variations of Prandtl numbers increase. Moreover, the velocity profiles increase when the variations of mixed convection and magnetohydrodynamics are increased. The temperature profiles are decreased for all variations of Prandtl numbers, mixed convection and magnetohydrodynamics.